2010
DOI: 10.3109/02841861003649224
|View full text |Cite
|
Sign up to set email alerts
|

Datamining approaches for modeling tumor control probability

Abstract: Background Tumor control probability (TCP) to radiotherapy is determined by complex interactions between tumor biology, tumor microenvironment, radiation dosimetry, and patient-related variables. The complexity of these heterogeneous variable interactions constitutes a challenge for building predictive models for routine clinical practice. We describe a datamining framework that can unravel the higher order relationships among dosimetric dose-volume prognostic variables, interrogate various radiobiological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 48 publications
(66 reference statements)
0
33
0
1
Order By: Relevance
“…1,[6][7][8] Therefore, the discovery of novel agents or signaling pathway targets that could prevent recurrence after definitive treatment has become increasingly important. [9][10][11][12][13] Preclinical findings have implicated cardiac medications such as angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs), which are in wide use as antihypertensive agents, in tumor growth and cancer progression. [14][15][16][17][18] Some clinical investigations indicated that receipt of ACEIs or ARBs was associated with improved outcomes among patients with prostate, hepatocellular, pancreatic, breast, or bladder cancer, [19][20][21][22][23][24] but others have not.…”
Section: Introductionmentioning
confidence: 99%
“…1,[6][7][8] Therefore, the discovery of novel agents or signaling pathway targets that could prevent recurrence after definitive treatment has become increasingly important. [9][10][11][12][13] Preclinical findings have implicated cardiac medications such as angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs), which are in wide use as antihypertensive agents, in tumor growth and cancer progression. [14][15][16][17][18] Some clinical investigations indicated that receipt of ACEIs or ARBs was associated with improved outcomes among patients with prostate, hepatocellular, pancreatic, breast, or bladder cancer, [19][20][21][22][23][24] but others have not.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has previously been used in radiation oncology for a variety of problems, from quality assurance to outcome prediction 20, 21, 22, 23, 24, 25, 26. In circumstances where the event being analyzed is relatively uncommon, machine learning algorithms are advantageous in magnifying events.…”
Section: Introductionmentioning
confidence: 99%
“…Four regions are shown in the figure representing high/low risks of local failure with high/low confidence levels, respectively. Note that cases falling within the classification margin have low confidence prediction power and represent intermediate-risk patients, i.e., patients with "border-like" characteristics that could belong to either risk group [26].…”
Section: Kernel-based Modeling Examplementioning
confidence: 99%
“…Separable cases could be modeled by linear kernels while non-separable cases are modeled by nonlinear kernels that allow for separability of the data but at the expense of increased dimensionality. This step could be preceded by a variable selection process and the generalizability of the model is evaluated using resampling techniques as discussed below [26].…”
Section: Data Setmentioning
confidence: 99%